2012
DOI: 10.1080/03098265.2011.641109
|View full text |Cite
|
Sign up to set email alerts
|

Public Scholarship Student Projects for Introductory Environmental Courses

Abstract: This paper presents a model project for introductory undergraduate courses that develops students as citizens contributing scholarship to public discussions of environmental issues. In this field-based project, students actively and independently engage with an environmental issue and present their project experience to a relevant public forum. In two implementations of the project, we find that the project succeeds at each of five goals: exposing students to public scholarship, connecting course material to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Several studies indicate that students feel positive emotions such as enjoyment (Kern & Carpenter, 1984 ; Scott et al, 2019 ; Van Loon, 2019 ) during field‐based instruction. However, other research has found that students can also express negative emotions during field instruction such as frustration (Baum et al, 2012 ), boredom (Goulder et al, 2013 ; Orion & Hofstein, 1994 ), and even fear (Brenner et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies indicate that students feel positive emotions such as enjoyment (Kern & Carpenter, 1984 ; Scott et al, 2019 ; Van Loon, 2019 ) during field‐based instruction. However, other research has found that students can also express negative emotions during field instruction such as frustration (Baum et al, 2012 ), boredom (Goulder et al, 2013 ; Orion & Hofstein, 1994 ), and even fear (Brenner et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…They require intensive planning, organization, and a unique level of adaptability from instructors who may lack support from their institutions or experience in facilitating such courses (Fleischner et al, 2017 ). Additionally, students occasionally find field experiences to be frustrating (Baum et al, 2012 ), anxiety‐inducing (Cotton, 2009 ), or even boring (Boyle et al, 2007 ). Students who identify with minoritized races/ethnicities and other identities can sometimes feel uncomfortable, a lack of belonging, or even unsafe in outdoor learning environments (Demery & Pipkin, 2021 ; Malm et al, 2020 ; O’Brien et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%